Determinan penggunaan sistem akuntansi pemerintah desa: Analisis keperilakuan menggunakan UTAUT - Dicky Andriyanto; Zaki Baridwan; Imam Subekti (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2019)
ABSTRACT This study aims to examine the relationship between the determinants of the use of accounting information systems in village financial management through behavioral aspects using the UTAUT model including performance expectancy, effort expectancy, social influence, and facilitating condition on behavioural intention. This study uses quantitative methods and data collection using a questionnaire. The study population was village offices in Banyuwangi Regency, while the samples used in this study used judgment sampling techniques. The collected data was analyzed using SmartPLS ver.2.0.M3. The results showed that performance expectancy, effort expectancy, and facilitating conditions had a positive and significant effect on behavioural intention using the system, while the social influence on behavioural intention using the system was not supported. In addition, the effects of male or female gender as well as the effects of masculine or feminine gender as moderating are not supported.